2017
DOI: 10.1371/journal.pone.0187144
|View full text |Cite
|
Sign up to set email alerts
|

Radiotherapy and chemotherapy change vessel tree geometry and metastatic spread in a small cell lung cancer xenograft mouse tumor model

Abstract: BackgroundTumor vasculature is critical for tumor growth, formation of distant metastases and efficiency of radio- and chemotherapy treatments. However, how the vasculature itself is affected during cancer treatment regarding to the metastatic behavior has not been thoroughly investigated. Therefore, the aim of this study was to analyze the influence of hypofractionated radiotherapy and cisplatin chemotherapy on vessel tree geometry and metastasis formation in a small cell lung cancer xenograft mouse tumor mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Typically, the variations between groups in the mean values of primary tumor size measured on different days are considered to be indicators of differences in, for example, the effectiveness of a drug treatment [3][4][5][6]. Sometimes data from these experiments are fitted to mathematical growth functions to describe and predict the growth of the tumor [7][8][9]. This experimental procedure promises well-defined reproducible results and generates new insights into metastasis formation when mathematical modeling is applied [10].…”
Section: Introductionmentioning
confidence: 99%
“…Typically, the variations between groups in the mean values of primary tumor size measured on different days are considered to be indicators of differences in, for example, the effectiveness of a drug treatment [3][4][5][6]. Sometimes data from these experiments are fitted to mathematical growth functions to describe and predict the growth of the tumor [7][8][9]. This experimental procedure promises well-defined reproducible results and generates new insights into metastasis formation when mathematical modeling is applied [10].…”
Section: Introductionmentioning
confidence: 99%
“…The role of vascular endothelial growth factor (VEGF) in these processes has resulted in it becoming an attractive target for accumulation at the tumor site [88,100]. Co-delivery of vessel normalizing drugs, vasodilators, and remodeling of the cancer-associated vasculature have also become prominent approaches to improving the accumulation of nanomaterials at the tumor site, with varying levels of success reported [101,102,103].…”
Section: Gathering At the Tumor Sitementioning
confidence: 99%
“…In terms of delivering nanomedicines across the endothelial barrier, a number of methods have been developed to improve the rate of extravasation and thus accumulation within the tumor mass. Recent efforts have demonstrated that the EPR effect may be improved through altering blood vessel geometry [102], normalizing vasculature [101], remodeling [103], and vessel pruning [123]. Microbubble cavitation can also be used to disrupt endothelial barriers and increase flow of material from vasculature into the tumor mass [124].…”
Section: Gathering At the Tumor Sitementioning
confidence: 99%
“…This means that in a metastatic setting, the organ/tissue that permits cancer cell seeding and growth likely plays a significant role in the vascular microenvironment, and consequently could impact drug delivery, distribution, and efficacy [42][43][44][45][46][47][48][49][50]. (iii) Treatments can affect vessel growth, structure, and function, adding to the complexity of vascular heterogeneity, which will change as a function of time after treatment is initiated [51,52]. Regardless of the root cause of vascular heterogeneity (i.e., location of disease burden or therapeutic implications), when evaluating a drug candidate's ability to reach and penetrate within a given tumor, at the very least, the vessel microenvironment must be considered, and it is insufficient to investigate in the context of just one site of tumor growth if the goal is to obtain meaningful therapeutic results in late-stage patients.…”
Section: Introductionmentioning
confidence: 99%